PELATIHAN KOMUNIKASI EFEKTIF DAN ETIKA PROFESIONAL BAGI PETUGAS ADMINISTRASI RUMAH SAKIT: IMPLEMENTASI EVALUASI SERTIFIKASI KOMPETENSI - Mahardika, Rosliana Mahardika; Joanna, Petricia Like (ICON Publisher, 2025)
The Effective Communication and Professional Ethics Training for Hospital Administrative Staff aims to enhance interpersonal and professional competencies to support the quality of hospital administrative services. The program was implemented through several structured stages, including needs assessment, the development of andragogy-based training modules, implementation of workshops, post-training mentoring, and comprehensive evaluation. The evaluation method employed a pre-test and post-test design to assess improvements in communication skills and understanding of professional ethics. The results indicated an average participant score increase of 45.2%, with 85% of participants demonstrating improved communication skills and 88% showing enhanced understanding of professional ethics. Additionally, administrative service efficiency increased by 20%, and patient satisfaction improved by 15%. The program effectively strengthened the competencies of non-medical human resources, fostered a professional and ethical work culture, and contributed to the continuous improvement of hospital service quality.